Branding Bali`s Spiritual Tourism: Content Strategies for Sustainable Tourism - Ni Luh Ketut Ayu Sudha Sucandrawati; Anak Agung Elik Astari; Pande Gde Bagus Naya Primananda; Ni Made Yusmini (Global Research Collaboration, 2026)
This study examines the effects of Spiritual Tourism and Content Marketing on Destination Competitiveness through the mediating role of Competitive Advantage in Bali’s spiritual tourism destinations. The research seeks to explain how spiritual and cultural assets can be transformed into sustainable competitive resources in the digital tourism era. A quantitative explanatory research design was employed using a survey of 219 domestic and international tourists who had participated in melukat spiritual tourism activities in Bali. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The results indicate that Spiritual Tourism and Content Marketing have significant positive effects on Competitive Advantage and Destination Competitiveness. Competitive Advantage also has a significant positive effect on Destination Competitiveness and partially mediates the relationships between Spiritual Tourism and Competitiveness, as well as between Content Marketing and Competitiveness. Among all direct relationships, Spiritual Tourism demonstrates the strongest influence on Competitive Advantage, emphasizing the strategic value of authentic spiritual experiences in strengthening destination competitiveness. This study extends the Resource-Based View by positioning spiritual and cultural assets as strategic resources capable of generating sustainable competitive advantage. It also introduces a digital-spiritual alignment perspective that integrates spiritual authenticity, content marketing, and destination competitiveness within a single framework. The findings offer valuable insights for tourism stakeholders seeking to enhance competitiveness while preserving cultural and spiritual integrity.